Peripheral Arterial Disease in Patients Presenting with Acute Coronary Syndrome in Six Middle Eastern Countries - Hassan A. Al-Thani; Ayman El-Menyar; Mohammad Zubaid; Wafa A. Rashed; Mustafa Ridha; Wael Almahmeed; Kadhim Sulaiman; Ahmed Al-Motarreb; Haitham Amin; Jassim Al Suwaidi (International Journal of Vascular Medicine)
To describe prevalence and impact of peripheral arterial disease (PAD) in patients with acute coronary syndrome (ACS), data were collected over 5 months from 6 Middle Eastern countries. Patients were divided into 2 groups (with and without PAD). Out of 6705 consecutive ACS patients, PAD was reported in 177 patients. In comparison to non-PAD, PAD patients were older and more likely to have cardiovascular risk factors. They were more likely to have high Killip class, high GRACE risk score, and non-ST elevation ACS (NSTEACS) at presentation. Thrombolytics, antiplatelet use, and coronary intervention were comparable in both groups. When presented with ST-elevation myocardial infarction (STEMI), patients with PAD had worse outcomes, while in NSTEACS; PAD was associated with higher rate of heart failure in comparison to non-PAD patients. In diabetics, PAD was associated with 2-fold increase in mortality when compared to non-PAD (P=0.028). After adjustment, PAD was associated with high mortality in STEMI (adjusted OR 2.6; 95% CI 1.23–5.65, P=0.01). Prevalence of PAD in ACS in the Gulf region is low. Patients with PAD and ACS constitute a high risk group and require more attention. PAD in patients with STEMI is an independent predictor of in-hospital death.